Spontaneous meningocele, a rare middle ear mass. - Gray, B G; Willinsky, R A; Rutka, J A; Tator, C H (American Journal of Neuroradiology, 1995)
This report describes the CT and MR findings in one patient with a spontaneous middle ear meningocele and a second patient with a middle ear meningoencephalocele possibly related to a large intracranial mass. High-resolution CT defined anatomic relation and bone destruction, and MR aided in tissue characterization.